Telecommunications networks: Towards smarter regulation and contracts?. Issue 3 (September 2017) - Gijrath, Serge J.H.
This article assesses the innovation policy objectives underlying the proposed European Union (EU) Telecom Single Market regulation considering disruptive technological developments. The article explores the network operator's dilemma how to deal with investments in a time where fundamental innovation comes from outside and the regulator's dilemma how to improve the conditions for access to the operators' networks and how to safeguard a level playing field. The EU measures with respect to two technological issues are discussed considering the EU's policy objectives with respect to the deployment of 5G and the goal to ensure very high-speed broadband access in the EU. Thought is given to the effectiveness of imposing active and passive infrastructure arrangements. A mix of regulatory measures is considered in moving towards smarter electronic communications networks regulation.